O contexto da gestão da inovação conforme o marco legal de ciência, tecnologia e inovação: as universidades, as patentes e um ambiente promotor de inovação - Verzola, Sabrina Carvalho (2021)
The management of technological innovation is premised on the performance of the State based on Science, Technology and Innovation policy in accordance with specific legislation in Brazil, which establishes the various legal instruments to drive and foster scientific, technological and innovation development. Consequently, public universities are the protagonists with regard to scientific production and patent filings, indicators that make up the spectrum of innovation as a dynamic and productive system to meet social demands and local and regional development. However, there is still the challenge of cooperation between the public and private sectors in the country, a factor that does not favour competitiveness and socioeconomic asymmetry in the country. Therefore, the objective of this thesis is to analyse the context of the institutionalisation of innovation according to the Legal Framework for Science, Technology and Innovation, and to present the Supera Innovation and Technology Park of Ribeirão Preto, located in the state of São Paulo, as a concrete case for the integration between the State, Universities, companies and society according to local factors and technological aptitude. In addition, this research establishes the relevance of the role of the State and Municipality for the institution and formulation of innovation policies for the creation of favourable environments for innovation. To that end, the thesis consists of an interdisciplinary and exploratory qualitative research through the application of document and bibliographic analysis methods and field study based on the legal and theoretical foundation for the respective contextualisation of the Supera Scientific and Technological Park in Ribeirão Preto, as an instrument for the creation of favourable environments for innovation and an alternative for the reduction of socioeconomic inequalities. It is worth highlighting the interdisciplinary nature of the Science, Technology and Society field for the application of the Legal Framework for Science, Technology and Innovation and for Legal Sciences for the purpose of effective integration and the democratic participation of society. The intention is to underpin the discussion pertinent to solutions for social demands in addition to legal mechanisms relevant to the management of innovation, such as technological extension and social technology as a contribution from the Science, Technology and Society field.